Prevalence and Mortality of Moderate or Severe Mitral Regurgitation Among Patients Undergoing Percutaneous Coronary Intervention With or Without Heart Failure: Results From CIN Study With 28,358 Patients - Huang, Haozhang; Liu, Jin; Bao, Kunming; Huang, Xiaoyu; Huang, Dehua; Wei, Haiyan; Remutula, Nuerbahaer; Tuersun, Tilakezi; Lai, Wenguang; Li, Qiang; Wang, Bo; He, Yibo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims This study investigated the prevalence and mortality associated with moderate or severe mitral regurgitation (MR) among patients undergoing percutaneous coronary intervention (PCI), with or without heart failure (HF). Methods We analysed patients undergoing PCI without mitral valve surgery from the Cardiorenal ImprovemeNt (CIN) study (ClinicalTrials.gov NCT04407936). Patients without echocardiography to determine MR occurrence or lacking follow-up death data were excluded. Primary endpoints were 1-year and long-term all-cause mortality, with a median follow-up time of 5.0 years (interquartile range: 3.1–7.6). Results Of 28,358 patients undergoing PCI treatment [mean age: 62.7 ± 10.7; women: 6,749 (25.6%)], 3,506 patients (12.4%) had moderate or severe MR, and there was a higher rate of moderate or severe MR in HF group than non-HF group (28.8% vs. 5.6%, respectively). Regardless of HF conditions, patients with moderate or severe MR were older and worse cardio-renal function, and significantly increased 1-year mortality [adjusted hazard ratio (aHR): 1.82, 95% confidence interval (CI): 1.51–2.20], and long-term mortality [aHR: 1.43, 95% CI: 1.30–1.58]. There was no significant difference between patients with HF and non-HF (P for interaction > 0.05). Conclusions One-eighth patients undergoing PCI had moderate or severe MR. Furthermore, one-third and one-seventeenth experienced moderate or severe MR with worse cardiorenal function in the HF and non-HF groups and increased consistent mortality risk. Further studies should explore the efficacy of mitral interventional procedures for moderate or severe MR after PCI treatment, regardless of HF.